Study on the Effect of Moisture Content and Dry Density on Shear Strength of Silty Clay Based on Direct Shear Test - Qinrong Kang; Yuandi Xia; Xiaoshuang Li; Weizhong Zhang; Chaoran Feng (Advances in Civil Engineering)
Silty clay is a kind of clay with more powder group than sand group, and its shear strength is mainly influenced by moisture content, dry density, and particle gradation. In this study, the deformation characteristics of silty clay under different normal pressure conditions were investigated from the perspective of control variables through indoor direct shear experiments. The results of the study show that with the same guaranteed moisture content, it can be seen from the fitted curves that with the increase of dry density, the arrangement of soil particles becomes more compact, the cementation between soil particles is strengthened, the shear strength increases, the occlusal friction increases due to the change of arrangement between soil particles, and the angle of internal friction and cohesion are relatively larger; in addition, when the dry density is the same, with the increase of moisture content, the soil becomes softer, and the form of water in the soil particles changes. In addition, when the dry density is the same, as the moisture content increases, the soil becomes softer, the presence of water between the soil particles changes, resulting in the weakening of the occlusion between the soil particles, the shear strength decreases, and the cohesion and the angle of internal friction relatively decrease.